Plant Networks for Processing Recyclable Materials - DEMEESTER, Lieven (Institutional Knowledge at Singapore Management University, 2013)
We use a modified optimal market area model to examine how links between material recycling and other aspects of operations strategy can shape plant networks for the processing of recyclable materials. We characterize the complementarity of the recyclate ratio, defined as the maximum recycled content, with material versatility and miniscaling of recycling plants. We also observe that it is beneficial to coordinate investments in recycling- and production-related competencies because colocated recycling and production plants (minimills) eliminate recyclate transport. We therefore consider versatile miniplants, defined as a competency that factors in both material versatility and coordinated miniscaling of recycling and production plants, and capture how it complements both the recyclate ratio and localization of production plants, a competency that takes advantage of local adaptation and customer proximity. In numerical examples for rolled aluminum and nylon resin plant networks in Europe, we find that the complementarity effects are large, as they are for nylon resins, if recycling is nascent and challenging economically and if the plant network is too centralized at first to benefit much from an increased recyclate ratio or increased localization. We find that, for the nylon resin network, considering an investment in the recyclate ratio as part of a coordinated investment plan drives the emergence of a decentralized and localized minimill network, even though an increased recyclate ratio does not link directly with either decentralization or localization. We conclude that material recycling, versatile miniplants, and localization can fit well together in a forward-looking, sustainable operations strategy.